Juridical Review of Criminal Arrangements in the Case of Violent Theft - Amanda Dwi Priaguna; Henry Aspan; Fitria Ramadhani Siregar (International Journal of Society and Law, 2024)
Law enforcement in Indonesia has various kinds of legal issues with various scenarios and motives for criminal acts committed. One of them is the Crime of Theft with Violence. . In this case, the Crime of Theft with Violence is qualified as a theft that is included in the case of theft with aggravation regulated in Article 363 of the Criminal Code and Article 365 of the Criminal Code. The crime of theft with violence in positive law. Law enforcement against the crime of theft with violence and handing over cases of theft with vehicle violence that occur to law enforcement to be processed in accordance with the applicable legal provisions, where the punishment or criminal sanctions imposed on the perpetrator are expected to provide a deterrent effect to the perpetrator in accordance with the purpose of the crime. The obstacles in law enforcement in the crime of theft through violence are the victim who died, the perpetrator is a minor, the suspect easily escapes, and the perpetrator leaves evidence.